Mapping the priority conservation areas for three endangered Cupressaceae plants under climate change in China - Shen, Lei; Zhai, Duanqiang; Lu, Xinyong (Frontiers in Plant Science, 2025)
The establishment of conservation areas is an important strategy for endangered species conservation.In this study, we investigated the distributions of suitable habitat areas for three Level 1 endangered Cupressaceae plants (Metasequoia glyptostroboides, Glyptostrobus pensilis, and Thuja sutchuenensis) in China and used the Marxan model to delineate the priority conservation areas for each species. The results showed that M. glyptostroboides had the broadest suitable growing area under the current climate in China and is followed by G. pensilis, with an area of 91×10 4 km 2 , and T. sutchuensis had the smallest suitable habitat areas, at only 7×10 4 km 2 . Affected by climate change, the suitable ranges of these three Cupressaceae species moved largely northward at the middle and end of this century, with a latitudinal increase of 0.46-1.99°. T. sutchenensis will face extremely high extinction risk by the end of this century; 65.54% of its southern suitable habitat area will no longer be suitable for growth. Based on the effects of climate change, M. glyptostroboides priority conservation areas should be established in the Yangtze River Basin; G. pensilis priority conservation areas should be established in Guangdong, Guangxi, Fujian and Jiangxi; and T. sutchuenensis protection districts should be established at the intersection of the northeastern part of Sichuan Province and the northern part of Chongqing. This study helps to clarify the impact of climate change on endangered species.